2002
DOI: 10.1002/gps.617
|View full text |Cite
|
Sign up to set email alerts
|

Measuring change in psychiatric symptoms using the Neuropsychiatric Inventory: Nursing Home version

Abstract: Overall, the results of this study indicate that the clinician evaluating elderly psychiatric inpatients should interpret a change in the total score of less than 22 points with caution, because it may be due to measurement error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 20 publications
1
37
2
Order By: Relevance
“…For each symptom endorsed, the interviewer follows up with a series of questions to rate the frequency and severity of the disturbance (Cummings). For descriptive purposes, symptom severity was estimated by multiplying scores for frequency and severity within each NPI domain (e.g., Iverson et al, 2002;.…”
Section: Assessment Of Neuropsychiatric Symptomsmentioning
confidence: 99%
“…For each symptom endorsed, the interviewer follows up with a series of questions to rate the frequency and severity of the disturbance (Cummings). For descriptive purposes, symptom severity was estimated by multiplying scores for frequency and severity within each NPI domain (e.g., Iverson et al, 2002;.…”
Section: Assessment Of Neuropsychiatric Symptomsmentioning
confidence: 99%
“…Street et al, 2000;Clark et al, 2001;Tariot et al, 2001). In one of the few studies examining the psychometric properties of the NPI-NH, Iverson et al (2002) reported 72-hour test-retest reliability coefficients ranging from r ¼ 0.55 to r ¼ 0.88 for each of the 12 individual symptoms in a geriatric neuropsychiatric sample. This research further indicated that psychometric properties of the npi-nha change in scores of less than 22 points should be interpreted with caution, as this difference may not reflect a meaningful change between two NPI-NH scores.…”
mentioning
confidence: 98%
“…In addition, the total score increased as dementia-related disability worsened, individuals with mild dementia had a mean total score on the NPI of 5.80 (SD = 12.5), those with moderate dementia had a mean score of 8.8 (SD = 11.10), and those with severe dementia had a mean score of 10.6 (SD = 17.0) (Lyketsos et al 2002). The mean total NPI score increased dramatically, ie, 36.4 (SD = 24.5), among patients with moderate to severe dementia admitted to the hospital for the management of their disturbed behaviors (Iverson et al 2002). The prevalence data provide an idea of the total NPI score range but they do not explain the fl uctuating nature of BPSD.…”
Section: The Natural History Of the Bpsdmentioning
confidence: 94%